Level of soft skills proficiency among hospitality management students in the Philippines - Marina R. Dapnit; Joan M. Nebrida; Angelica D. Dungcayan; Jenelyn M. Milio; Zyra Ann T. Pawid; Riza L. Silvano; Romelia C. Tagami; Ranel F. Montemayor; Evangeline H. Castro (Journal of Rural Tourism, 2026)
Purpose – This study aims to assess the level of soft skills proficiency among Hospitality Management students at Nueva Vizcaya State University, Bambang, Nueva Vizcaya, focusing on communication, leadership, teamwork, problem-solving, and adaptability, as well as examining differences based on demographic profiles.Design/Methodology/Approach – A quantitative descriptive–correlational design was employed, involving 271 students selected through total population sampling. Data were collected using a structured questionnaire measuring multiple soft skill domains. Descriptive statistics and inferential analysis using F-tests were applied to determine proficiency levels and examine differences across variables such as age, gender, year level, parents’ occupation, and household income.Findings – The results indicate that students demonstrate moderate to high proficiency in key soft skills, with teamwork and problem-solving identified as the strongest competencies. Communication and adaptability emerged as areas requiring improvement. Age was found to have a significant influence on proficiency, with older students exhibiting higher skill levels. No significant differences were observed across gender, year level, parents’ occupation, or household income, suggesting relatively equitable development across these groups.Originality/Value – This study provides empirical insights into soft skills development within hospitality education, highlighting the importance of targeted interventions to enhance communication, leadership, and adaptability. It underscores the role of institutional support and experiential learning in preparing students for professional readiness in the hospitality industry.